Manual of perioperative care in adult cardiac surgery - Bojar, Robert M., 1951- (New Jersey : Wiley-Blackwell, 2020)
"It is essential that all individuals involved in the assessment and management of patients with cardiac surgical disease have a basic understanding of the disease processes that are being treated. This chapter presents the spectrum of adult cardiac surgical disease that is encountered in most cardiac surgical practices. The pathophysiology, indications for surgery, specific preoperative considerations, and surgical options for various diseases are presented. Diagnostic techniques and general preoperative considerations are presented in the next two chapters. Issues related to cardiac anesthesia and postoperative care specific to most of the surgical procedures presented in this chapter are discussed in Chapters 4 and 8, respectively. The most current guidelines for the evaluation and management of patients with cardiac disease can be obtained from the American College of Cardiology website (www.acc.org)"--
Synopsis of adult cardiac surgical disease -- Diagnostic techniques in cardiac surgery -- General preoperative considerations and preparation of the patient for surgery -- Cardiac anesthesia -- Cardiopulmonary bypass -- Myocardial protection -- Admission to the ICU and monitoring techniques -- Early postoperative care -- Mediastinal bleeding -- Respiratory management -- Cardiovascular management -- Fluid management, renal, metabolic, and endocrine problems -- Post-ICU care and other complications.
BIBINDX
Keywords: Cardiac Surgical Procedures; Perioperative Care -- methods; Handbook; Electronic books